Therapist Effects and Spiritually Oriented Psychotherapy - Sperry, Len (Open theology, 2016)
Research on therapist effectiveness (i.e., therapist effects) is important for spiritually oriented psychotherapy to mature and flourish as a specialty. Therapist effects are described and compared to treatment effects, and then a research-based profile of the effective therapist is sketched. This characterization is similar in both spiritually-oriented psychotherapy and secular psychotherapy, which has no spiritual orientation. The challenge for this specialty is for research to integrate both therapist effects and treatment effects to inform psychotherapy training. This discussion is framed within Alan Bergin‘s (1980) "hope" that the psychotherapy profession would become more comprehensive and more effective.